Veterinary public health capacity-building in India: A grim reflection of the developing world’s underpreparedness to address zoonotic risks - Kakkar, M.; Abbas. S.S.; Kumar, A.; Hussain, M.A.; Sharma, K.; Bhatt, P.M.; Zodpey, S. (2013)
Veterinary public health (VPH) is ideally suited to promote convergence between human, animal and environmental sectors. Recent zoonotic and emerging infectious disease events have given rise to increasing calls for efforts to build global VPH capacities. However, even with their greater vulnerability to such events, including their economic and livelihood impacts, the response from low and middle-income countries such as India has been suboptimal, thereby elevating global health risks. Addressing risks effectively at the human–animal interface in these countries will require a clear vision, consistent policies, strategic approach and sustained political commitment to reform and refine the current VPH capacity building efforts. Only then can the discipline serve its goal of disease prevention, poverty alleviation and support for sustainable livelihoods through improvements in human and animal health.